CULTURAL EXPERIENCES MELALUI “HOMESTAY BUDAYA” SEBAGAI PARIWISATA KREATIF - Fathimah Khoerudini (JURNAL ILMU MANAJEMEN, 2018)
This study is aimed to explore the concept of “Homestay Budaya” as a solution to the increasing competition in the tourism sector and at the same time as a place to preserve the culture, customs, politeness, and regional languages. This study uses the literature review method. Through this literature study, the concept of “Homestay Budaya” was found to be suitable with the expected goals. That is as a source of income for the country and the surrounding community, as well as preserving regional culture. “Homestay Budaya” will be managed through an android application which will make it easier for tourists to choose their homestay in all regions in Indonesia. The cultural homestay application is a tourist liaison with the local wisdom of all regions in Indonesia